Perlindungan Hukum terhadap Korban Kekerasan Seksual Berbasis Elektronik (KSBE) Pasca Sahnya UU TPKS - Muhammad Idwan; Aturkian Laia (INDO PUBLISHING, 2026)
Information technology developments have birthed a new form of cyber-faced sexual violence, namely Electronic-Based Sexual Violence (EBSV). This normative juridical research aims to analyze the legal framework of EBSV after the enactment of the TPKS Law, forms of victim protection, and implementation barriers. The novelty lies in the integrated analysis of three legal regimes (TPKS Law, ITE Law, Criminal Code) incorporating the latest implementing regulations, Government Regulation Number 30 of 2025 and Government Regulation Number 29 of 2025. The results indicate that the TPKS Law successfully fills legal lacunae and shifts the paradigm toward victim-oriented enforcement. However, its effectiveness remains hindered by regulatory disharmony, digital proof burdens, social stigma, and technical issues regarding victim trust funds. This study recommends regulatory harmonization, strengthening digital forensics capacity, and optimizing restitution mechanisms.